The Effect of Retirement on Income Distribution: A Comprehensive Income Approach - Burkhauser, Richard V.; Wilkinson, James T. (The Review of Economics and Statistics, 1983)
Richard V. Burkhauser, James T. Wilkinson, The Effect of Retirement on Income Distribution: A Comprehensive Income Approach, The Review of Economics and Statistics, Vol. 65, No. 4 (Nov., 1983), pp. 653-658